Dietary habits in adults during quarantine in the context of COVID-19 pandemic - Abbas, Ahmed M. (Obes Med, 2020)
• COVID-19 pandemic lead to stress conditions that can cause a dramatic change in our dietary habits. • Eating a well-balanced diet is the best way to get all the essential nutrients we need for normal immune function. • Poor quality sleep can negatively affect both physical and mental health.